Surface Finishing Theory and New Technology - Yang, Shengqiang; Li, Wenhui (Springer Berlin Heidelberg : Imprint: Springer, 2018)
This book focuses on the theory and techniques of free abrasive tool finishing technology. Providing analytical methods and practical technical references for the engineers involved in surface-finishing processes, it significantly contributes to improving part quality and performance while also promoting further developments in surface finishing technology. Combining a highly systematic approach, readability and novel content, it is a valuable resource for researchers and graduates working in mechanical engineering fields, especially in surface finishing.